A Comprehensive Model of the Spectrin Divalent Tetramer Binding Region Deduced Using Homology Modeling and Chemical Cross-linking of a Mini-spectrin - Li, Donghai (American Society for Biochemistry and Molecular Biology, 2010)
Spectrin dimer-tetramer interconversion is a critical contributor to red cell membrane stability, but some properties of spectrin tetramer formation cannot be studied effectively using monomeric recombinant domains. To address these limitations, a fused αβ mini-spectrin was produced that forms wild-type divalent tetramer complexes. Using this mini-spectrin, a medium-resolution structure of a seven-repeat bivalent tetramer was produced using homology modeling coupled with chemical cross-linking. Inter- and intramolecular cross-links provided critical distance constraints for evaluating and optimizing the best conformational model and appropriate docking interfaces. The two strands twist around each other to form a super-coiled, rope-like structure with the AB helix face of one strand associating with the opposing AC helix face. Interestingly, two tetramer site hereditary anemia mutations that exhibit wild-type binding in univalent head-to-head assays are located in the interstrand region. This suggests that perturbations of the interstrand region can destabilize spectrin tetramers and the membrane skeleton. The α subunit N-terminal cross-links to multiple sites on both strands, demonstrating that this non-homologous tail remains flexible and forms heterogeneous structures in the tetramer complex. Although no cross-links were observed involving the β subunit non-homologous C-terminal tail, several cross-links were observed only when this domain was present, suggesting it induces subtle conformational changes to the tetramer site region. This medium-resolution model provides a basis for further studies of the bivalent spectrin tetramer site, including analysis of functional consequences of interstrand interactions and mutations located at substantial molecular distances from the tetramer site.